Classifying industries into types of relative concentration - Ludwig von Auer; Andranik Stepanyan; Mark Trede (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2016)
When some industries are overrepresented in urban areas (urban concentration), some other industries must be overrepresented in rural areas (rural concentration). Existing measures of concentration do not distinguish between these different types of concentration. Instead, they rank industries according to their degree of concentration. However, knowing the concentration type is important, when investigating the forces of agglomeration that shape the geographical distribution of an industry. Therefore, the present paper proposes a new statistical approach that classifies each industry into one of seven different geographical patterns, five of which represent different types of concentration. The statistical identification of each industry's geographical pattern is based on two Goodman-Kruskal rank correlation coefficients. The power of our approach is illustrated by German employment data on 613 different industries in 412 regions.
Keywords: R10; R12; 330; Geographical Concentration; Archetypes; Confidence Region; Goodman-Kruskal Coefficient